2009
DOI: 10.1038/ki.2009.381
|View full text |Cite
|
Sign up to set email alerts
|

Nephrin mutations cause childhood- and adult-onset focal segmental glomerulosclerosis

Abstract: Mutations in the NPHS1 gene cause congenital nephrotic syndrome of the Finnish type presenting before the first 3 months of life. Recently, NPHS1 mutations have also been identified in childhood-onset steroid-resistant nephrotic syndrome and milder courses of disease, but their role in adults with focal segmental glomerulosclerosis remains unknown. Here we developed an in silico scoring matrix to evaluate the pathogenicity of amino-acid substitutions using the biophysical and biochemical difference between wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(87 citation statements)
references
References 40 publications
5
79
0
3
Order By: Relevance
“…The NPHS1 mutation of 3250insG, which leads to a frameshift and a truncated nephrin protein, V1084fsX1095, was previously reported and accepted as a pathological mutation (Lenk-keri et al, 1999;Santín et al, 2009;Lee et al, 2009). Santín et al (2009) considered that nonsense and frameshift mutations, which are predicted to result in a truncated protein, are classified as a severe mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NPHS1 mutation of 3250insG, which leads to a frameshift and a truncated nephrin protein, V1084fsX1095, was previously reported and accepted as a pathological mutation (Lenk-keri et al, 1999;Santín et al, 2009;Lee et al, 2009). Santín et al (2009) considered that nonsense and frameshift mutations, which are predicted to result in a truncated protein, are classified as a severe mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Santín et al (2009) considered that nonsense and frameshift mutations, which are predicted to result in a truncated protein, are classified as a severe mutation. In our study, the patient with a homozygous mutation of V1084fsX1095 presented generalized edema at six days after birth and marked hypoalbuminemia, with a serum albumin level of 4.6 g/L, suggesting that severe mutations cause a severe clinical phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The high percentage of NPHS2 missense variants represents a diagnostic challenge because in some cases it is difficult to differentiate between a disease-causing mutation and a neutral variant. We describe here an in silico sequence variant classification strategy for the NPHS2 amino acid substitutions based on the combination of different approaches previously reported for other genes (30,41,42), which takes into account (1) the analysis of control chromosomes, (2) the cosegregation with the disease in a family, (3) the biophysical and biochemical difference between wild-type and mutant amino acids (28), (4) the evolutionary conservation of the amino acid residue in orthologs (29,43,44), and (5) software that uses in silico predictors of pathogenic effect [Polyphen (45), SIFT (46)] and splice site [Neural Network (47)]. The accuracy of this in silico analysis was tested using previously described and classified podocin-amino acid substitutions.…”
Section: Discussionmentioning
confidence: 99%
“…Classically, mutations in the NPHS1 and NPHS2 genes have been distinguished by their implications in familial congenital (onset at birth to 3 month) and in childhood-onset (later than 3 month) cases, respectively (5,11). Furthermore, it has recently been shown that mutations in NPHS1 also account for a nonnegligible proportion of infantile, childhood and adult-onset SRNS cases (12)(13)(14). ADCK4 gene, which located on chromosome 19q13.2 and encodes the aarF domain containing kinase 4, is now well-known as a single-gene cause of SRNS (15)(16)(17).…”
Section: Case Presentationmentioning
confidence: 99%